2018
DOI: 10.1038/s41598-018-34684-1
|View full text |Cite
|
Sign up to set email alerts
|

Design of a novel cell-permeable chimeric peptide to promote wound healing

Abstract: Biological membranes are impermeable to almost all compounds having a molecular weight greater than 500 Da. Recently, cell penetrating peptides (CPPs) as delivery vehicles have attracted great interest in the medical sector for the development of novel therapeutic agents or cosmetic products. Herein, a wound healing promoting sequence, namely Tylotoin, was covalently coupled with a cell penetrating peptide to improve the delivery of Tylotoin across cellular membranes. Indeed, internalization studies indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 51 publications
(65 reference statements)
4
24
0
Order By: Relevance
“…Notably, the averaged fluorescence intensity measured for CF‐sC18‐I‐Pc was about 900 % higher than for CF‐sC18 (Figure C) which is in accordance with results from microscopic uptake studies (Figures S2A and S2C, respectively). In previous work, we have demonstrated that sC18 as well as a truncated version named sC18* are able to induce and stabilize helix formation, when attached to peptide sequences . The presence of such helical structures is very important for the peptide–lipid interaction at the plasma membrane surface, and thus, these peptide hybrids are often characterized by increased cellular uptake and biological activity in comparison to sC18 alone.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the averaged fluorescence intensity measured for CF‐sC18‐I‐Pc was about 900 % higher than for CF‐sC18 (Figure C) which is in accordance with results from microscopic uptake studies (Figures S2A and S2C, respectively). In previous work, we have demonstrated that sC18 as well as a truncated version named sC18* are able to induce and stabilize helix formation, when attached to peptide sequences . The presence of such helical structures is very important for the peptide–lipid interaction at the plasma membrane surface, and thus, these peptide hybrids are often characterized by increased cellular uptake and biological activity in comparison to sC18 alone.…”
Section: Resultsmentioning
confidence: 99%
“…The present study aimed to explore synthetic ECM-mimicking hydrogels based on CLP and CLP-RGD blocks conjugated to a poly(ethylene glycol) template (PEG-CLP and PEG-CLP-RGD, respectively), as well as to investigate how these artificial, all-synthetic substrates affect primary cerebellar cell organization, composition, motility and function. Recently, chimeric peptides have emerged as a promising synthetic biological strategy for medical applications [20], and we have already reported the application of PEG-CLP-RGD hydrogels for cancer cell models ( [21], in revision). Additionally, we aimed to elucidate the role of the viscoelasticity of the ECM-mimicking substrate.…”
Section: Introductionmentioning
confidence: 99%
“…CPP have been combined with a compound such as epidermal growth factor to promote keratinocyte proliferation for skin regeneration or wounds healing by increasing translocation of regenerative compounds into cells. [36][37][38][39] CPP have been combined with BMP2 to promote bone differentiation or to restore bone defects in the bone grafts of dental implants. 40 In addition, CPP-complexes with 41 CPP-SOCS3 complexes have been shown to suppress acute inflammation in multiple.…”
Section: Discussionmentioning
confidence: 99%